Comprehensive Behavioral Analysis of Activating Transcription Factor 5-Deficient Mice - Umemura, Mariko; Ogura, Tae; Matsuzaki, Ayako; Nakano, Haruo; Takao, Keizo; Miyakawa, Tsuyoshi; Takahashi, Yuji (Frontiers in Behavioral Neuroscience, 2017)
Activating transcription factor 5 (ATF5) is a member of the CREB/ATF family of basic leucine zipper transcription factors. We previously reported that ATF5-deficient (ATF5-/-) mice demonstrated abnormal olfactory bulb development due to impaired interneuron supply. Furthermore, ATF5-/- mice were less aggressive than ATF5+/+ mice. Although ATF5 is widely expressed in the brain, and involved in the regulation of proliferation and development of neurons, the physiological role of ATF5 in the higher brain remains unknown. Our objective was to investigate the physiological role of ATF5 in the higher brain. We performed a comprehensive behavioral analysis using ATF5-/- mice and wild type littermates. ATF5-/- mice exhibited abnormal locomotor activity in the open field test. They also exhibited abnormal anxiety-like behavior in the light/dark transition test and open field test. Furthermore, ATF5-/- mice displayed reduced social interaction in the Crawley’s social interaction test and increased pain sensitivity in the hot plate test compared with wild type. Finally, behavioral flexibility was reduced in the T-maze test in ATF5-/- mice compared with wild type. In addition, we demonstrated that ATF5-/- mice display disturbances of monoamine neurotransmitter levels in several brain regions. These results indicate that ATF5 deficiency elicits abnormal behaviors and the disturbance of monoamine neurotransmitter levels in the brain. The behavioral abnormalities of ATF5-/- mice may be due to the disturbance of monoamine levels. Taken together, these findings suggest that ATF5 -/- mice may be a unique animal model of some psychiatric disorders.